Sports Hijab: Keeping Healthy Suggestion, Muslimah, and Islamic Da’wa Practice - Fathayatul Husna (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
This paper examined the fulfillment of shar’i sportswear facilities for Muslim women, with a case study in Living Sports Hijab. The main question in this research is how Muslim women's activities to exercise in public spaces are fulfilled by shar’i sportswear from Livigi Sports Hijab? To answer this question, the authors collected data through interviews, literature studies, and combined it with online data. This article examined by using a qualitative descriptive method. The results of this study that Livigi Sports Hijab is one of the best brands in Indonesia that provides shar’i sportswear facilities for Muslim women. The presence of Living Sports Hijab not only gives Muslim women freedom to exercise in public spaces but also supports Muslim women to maintain their health by exercising. This showed that women have the same rights as men to use public spaces as access to exercise. In addition, Living Sports Hijab also spread Islamic da’wa through social media accounts and through shar’i sportswear. Not only around Islamic da'wa, but also shared campaign to become a strong Muslimah. Thus, the conclusion of Living Sports Hijab as the object of this study showed that Muslim women also negotiate public spaces for exercise. Therefore, this paper contributes to enriching new discourses related to Muslim women, public spaces, and Islamic da’wa in the contemporary era.